Gambaran Tindakan Keperawatan pada Masalah Keperawatan Utama Anak dengan Kejang Demam di RS Perkebunan Wilayah Karesidenan Besuki - Rofifah Isro'atus Sabella; Lantin Sulistyorini; Peni Perdani Juliningrum (Pustaka Kesehatan, 2022)
Febrile Seizures are seizures that appear during fever because it is caused by an intracranial process, as there are infections of the respiratory tract, ears, and digestive tract. According to the SIKI guidebook, there are several nursing actions performed and integrated into dealing with hyperthermia that is classified into observational, therapeutic, educational, and collaborative actions. The purpose of this study was to determine the main nursing problems, nursing actions, and nurse innovations in febrile seizures by nurses. Research design uses a quantitative descriptive, retrospective approach, with sampling total sampling techniques. The research sample in this study was 113 children’s medical record data with febrile seizures at the age of 6 months to 5 years. The research instrument uses a checklist sheet based on the manual SIKI by PPNI 2018. The results of this study were 93,8% hyperthermia nursing problems, the actions of the observations were 7 actions, therapeutic 13 actions, education 3 actions, collaboration 5 actions, and no action on innovation in children with febrile seizures. To treat febrile seizures, research is needed on the causes of fever that occur in children with febrile seizures.